Pengaruh Literasi Keuangan Dan Strategi Penetapan Harga Terhadap Kinerja Keuangan Pada Umkm Di Lombok Tengah - Azhari, Ferawati; Animah, Animah (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the effect of financial literacy and pricing strategy on the financial performance of MSMEs in Central Lombok, specifically in the beauty salon sector. This research uses a quantitative approach with a survey method on 64 MSMEs in the salon sector in Central Lombok. The data were analyzed using the Partial Least Squares (PLS) method with the help of SmartPLS 4 software to test the relationships between the variables studied. The results show that financial literacy and pricing strategy have a positive and significant impact on the financial performance of MSMEs. The better the financial understanding and the more effective the pricing strategy applied, the better the financial performance of MSMEs. These findings emphasize that improving financial literacy and implementing the right pricing strategy are crucial factors in enhancing competitiveness and sustainability of MSMEs. Therefore, understanding financial recordkeeping, budgeting, and setting the right prices is vital for business efficiency and sustainability.